Implementasi Manajemen Pendidikan Islam dalam Menanamkan Pendidikan Karakter bagi Anak Panti Asuhan Al Kausar di Sangatta Utara - Muhammad Ibnu Faruk Fauzi (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to describe the implementation of Islamic education management in instilling character education for children at Al Kausar Orphanage in Sangatta Utara. The background of this research lies in the crucial role of religious social institutions in shaping the character of the younger generation, especially children living in orphanages. This research employs a qualitative approach using field research methods. Data were collected through observation, in-depth interviews, documentation, and surveys. The results show that the implementation of Islamic education management at Al Kausar Orphanage includes planning moral development programs, organizing the roles of caregivers and volunteers, executing activities based on habituation and role modeling, and conducting regular evaluations of the children’s character development. The main supporting factors include the commitment of the caregivers, a religious and caring environment, and community support, while the inhibiting factors involve limited human resources, operational funding constraints, and the psychological challenges faced by the children